Phased Treatment Strategies for Cerebral Ischemia Based on Glutamate Receptors - Sun, Yongjun; Feng, Xue; Ding, Yue; Li, Mengting; Yao, Jun; Wang, Long; Gao, Zibin (Frontiers in Cellular Neuroscience, 2019)
Extracellular glutamate accumulation following cerebral ischemia leads to overactivation of glutamate receptors, thereby resulting in intracellular Ca2+ overload and excitotoxic neuronal injury. Multiple attempts have been made to counteract such effects by reducing glutamate receptor function, but none have been successful. In this minireview, we present the available evidence regarding the role of all types of ionotropic and metabotropic glutamate receptors in cerebral ischemia and propose phased treatment strategies based on glutamate receptors in both the acute and post-acute phases of cerebral ischemia, which may help realize the clinical application of glutamate receptor antagonists.